2018
DOI: 10.1016/j.heliyon.2018.e00804
|View full text |Cite
|
Sign up to set email alerts
|

BACCHUS: A randomised non-comparative phase II study of neoadjuvant chemotherapy (NACT) in patients with locally advanced rectal cancer (LARC)

Abstract: BackgroundChemoradiation (CRT) or short-course radiotherapy (SCRT) are standard treatments for locally advanced rectal cancer (LARC). We evaluated the efficacy/safety of two neoadjuvant chemotherapy (NACT) regimens as an alternative prior to total mesorectal excision (TME).Methods/designThis multi-centre, phase II trial in patients with magnetic resonance imaging (MRI) defined high-risk LARC (>cT3b, cN2+ or extramural venous invasion) randomised patients (1:1) to FOLFOX + Bevacizumab (Arm 1) or FOLFOXIRI + bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
0
25
0
4
Order By: Relevance
“…adding neoadjuvant chemotherapy to CRT [19] and in two studies where chemotherapy alone was used [20,21]. However, a recent study from the Netherlands dismissed the prognostic value of NAR-score; single pathological parameters (pT, pN) have similar concordance (C-index of 0.663 and 0.655), i.e.…”
mentioning
confidence: 99%
“…adding neoadjuvant chemotherapy to CRT [19] and in two studies where chemotherapy alone was used [20,21]. However, a recent study from the Netherlands dismissed the prognostic value of NAR-score; single pathological parameters (pT, pN) have similar concordance (C-index of 0.663 and 0.655), i.e.…”
mentioning
confidence: 99%
“…The BACCHUS trial showed early exposure to a triplet NACT combination, FOLFOXIRI with bevacizumab did not impact adversely on compliance or surgical morbidity. 45 The Chinese randomized FOWARC study in rectal cancer show neoadjuvant FOLFOX without chemoradiotherapy achieves similar tumor downstaging rates of R0 resection, with lower rates of surgical morbidity than CRT. 43 Ongoing trials include a randomized phase II trial exploring the best sequence of CRT and NACT (NCT02008656) and the PROSPECT trial investigating NACT with FOLFOX and a selective use of CRT in early-stage patients with cT2N1 and cT3N0-1 rectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In rectal cancer, a single published randomized phase III trial was identified, 43 and two randomized phase II studies, 44,45 nine prospective phase II, [46][47][48][49][50][51][52][53][54] and a single retrospective study 55 have been presented/published (►Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…NAC could compensate for such shortcomings, potentially yielding better survival outcomes. However, only few studies have reported the efficacy of NAC for LALRC without NACRT [7, 8].…”
Section: Introductionmentioning
confidence: 99%